2020
DOI: 10.1088/1757-899x/802/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alumina on mechanical behavior of Al 6064 alloy

Abstract: Need in the development of new materials with excellent properties are growing day by day. Composite materials are the simple and better way to accomplish materials with superior properties. Aluminium metal matrix composites due to their high strength to weight ratio, low cost, improved electrical conductivity and good tribological properties are broadly produced and used in various engineering applications in the area of automobile, aerospace and military engineering. In the present paper an attempt has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It was observed that the stirring time and processing temperature have significant effects on the mechanical properties (elastic modulus and harness) and microstructure of the composites. Kumar et al [19] analysed the mechanical behaviour of the metal matrix composites by changing the composition of the reinforcements. They observed that the 7.5wt% Al2O3 shows enhanced mechanical properties such as hardness, tensile strength and toughness and also uniform distribution of the reinforcement particles.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the stirring time and processing temperature have significant effects on the mechanical properties (elastic modulus and harness) and microstructure of the composites. Kumar et al [19] analysed the mechanical behaviour of the metal matrix composites by changing the composition of the reinforcements. They observed that the 7.5wt% Al2O3 shows enhanced mechanical properties such as hardness, tensile strength and toughness and also uniform distribution of the reinforcement particles.…”
Section: Introductionmentioning
confidence: 99%
“…Finding or detecting the flow pattern of the SiC particles was not feasible because of the elevated processing temperature in the stir casting process. [17]. Streak photography is the visualization experiment to trace a particle which helps to find out the flow pattern of the reinforced particles and the presence of clustering region of the fluid.…”
Section: Introductionmentioning
confidence: 99%